ISSUES OF IMPROVING COST ACCOUNTING IN HEALTHCARE INSTITUTIONS - Shanasirova Nodira Abdullayevna (Journal Park Publishing, 2023)
In the article, research was conducted on the issues of improving cost accounting in healthcare institutions, and conclusions and suggestions were formed within the topic.
Keywords: healthcare, budget organization, accounting, cost, funds.